Tailoring the fibre-to-matrix interface using click chemistry on carbon fibre surfaces. Issue 22 (24th May 2017) - Servinis, Linden; Beggs, Kathleen M.; Gengenbach, Thomas R.; Doeven, Egan H.; Francis, Paul S.; Fox, Bronwyn L.; Pringle, Jennifer M.; Pozo-Gonzalo, Cristina; Walsh, Tiffany R.; Henderson, Luke C.
Abstract : A convenient and effective strategy to control the surface chemistry of carbon fibres is presented, comprising electro-chemical reduction of aryl diazonium salts onto the surface, followed by 'click chemistry' to tether the desired surface characteristic of choice. Abstract : A convenient and effective strategy to control the surface chemistry of carbon fibres is presented, comprising electro-chemical reduction of aryl diazonium salts onto the surface, followed by 'click chemistry' to tether the desired surface characteristic of choice. The power of this approach was demonstrated by engineering a small-molecule interface between carbon fibre and an epoxy matrix improving interfacial shear strength by up to 220%, relative to unmodified control fibres. The techniques used in this work do not impede the fibre performance in tensile strength or Young's modulus. This work provides a platform upon which any carbon fibre-to-resin interface can be easily and rapidly designed and implemented.